La mise en scène nocturne de la montagne en Chine. Enquêtes sur le spectacle son et lumière Impressions de Liusanjie (Guilin, Province du Guangxi) - Wei Xiang; Philippe Bachimon (Revue de Géographie Alpine)
As the tourism sector grows as a whole, night-time tourism is playing a significant complementary role in the regional development not only of urban areas, but also of the mountainous areas that surround them. Following twelve years of very rapid development, night-time tourist products in China’s mountainous Scenic Areas are offered primarily in the form of outdoor performances. Based on a case study of the show Impressions of Liu Sanjie, which in 2004 became China's first outdoor production and has paved the way for other night-time tourist products in China’s mountainous Scenic Areas, we consider the nature and effects of this form of entertainment. Twelve years on, what have been the economic, social, cultural and environmental consequences for the region? How do night-time performances contribute (or not) to local development? And what is the relationship between the image of Liu Sanjie and the local identity of Guilin? This article attempts to provide answers to such questions.